IMPLEMENTASI PERIZINAN BERUSAHA BERBASIS RESIKO DALAM PENGEMBANGAN EKONOMI DI KABUPATEN MANGGARAI - Bani, Ferdinandus; Klara seke, Sonia; Lobo, Ferdinandus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Risk-based business licensing is an increasingly important approach in economic development in Indonesia, including in Manggarai Regency. This licensing system aims to convey the licensing process by considering the level of risk posed by a business activity. In this context, licensing functions as a legal instrument to regulate and supervise activities that have the potential to affect the public interest, as well as protect the community and the environment. However, challenges such as complicated bureaucracy and transparency often hinder the effectiveness of this system. Therefore, this study aims to identify the problems faced by the Manggarai Regency Regional Government in the implementation of risk-based licensing, as well as the urgency of forming Regional Regulations that regulate these matters. In addition, this study will also discuss the philosophical, sociological, and juridical foundations of the formation of these regulations, as well as the goals and scope of their regulation. It is hoped that with clear and transparent regulations, the risk-based licensing system can encourage local economic growth, increase the number of registered businesses, and create a conducive investment climate in Manggarai Regency